Influences of the Cloud Shape of Fuel-Air Mixtures on the Overpressure Field. (27th April 2016) - Bai, Chunhua; Wang, Ye; Li, Jianping; Chen, Mingsheng
Abstract : This paper presents an experiment system in the open field, which comprises a charge structure (approximately 166.2 kg), a high-speed camera subsystem, and a pressure measurement subsystem. Through a series of experiments under the cylindrical clouds with different diameters, heights, and diameter-to-height ratios (D  : H ), the influences of various cloud shapes on the overpressure field were analyzed and discussed. Based on the experimental results, the overpressure field was divided into two zones: detonation wave zone and shock wave zone. It is found that the overpressure of shock waves at the same distance from the explosion center increased with the diameters, but the variations of heights had little impact on the overpressure. Therefore, the pancake-shaped cloud of fuel-air mixtures is the optimal shape for obtaining the wider overpressure field. Moreover, it is found that the overpressure field gets the maximum under the diameter-to-height ratios of 5.7 in the same distance within the studied range.